Proposals for Second Five Year Plan Fisheries Department Government of Madhya Bharat - Planning Commission (Planning Commission, 1949)
Development and organisation of Fisheries in this State started shortly after the formation of Madhya Bharat in 1949, when the Fisheries Department was created. This Department took up a survey of the whole State to find out (i) natural resources of fish and availability of different varieties of fish in various areas, (ii) breeding grounds of selected varieties of fish and (iii) conditions of local fishermen. This preliminary survey showed that there is sufficient scope for the development of fisheries in the State, in all its aspects viz., conservation, augmentation and utilization of fish crop.
Government of Madhya Bharat